Congenital contractural arachnodactyly complicated with aortic dilatation and dissection: Case report and review of literature. (14th May 2015) - Takeda, Norifumi; Morita, Hiroyuki; Fujita, Daishi; Inuzuka, Ryo; Taniguchi, Yuki; Imai, Yasushi; Hirata, Yasunobu; Komuro, Issei
<x xml:space="preserve">Abstract</x> Congenital contractural arachnodactyly (CCA) is a connective tissue disease caused by mutations of the FBN2, which encodes fibrillin‐2. CCA patients have a marfanoid habitus; however, aortic dilatation and/or dissection as observed in Marfan syndrome have been rarely documented. Here, we report on a Japanese familial case of CCA resulting from a FBN2 splicing mutation (IVS32+5g→a), which leads to exon 32 being skipped, and the patients developed aortic dilatation and type A dissection. Although CCA patients have been believed to have favorable prognoses, repetitive aortic imaging studies must be performed in some patients to detect possible aortic disease early, and genetic testing of FBN2 might be useful to identify such high‐risk patients. © 2015 Wiley Periodicals, Inc.